Cultural planning, an urban renaissance? - Evans, Graeme. 4 0 16; 5 (London ;;New York : Routledge, 2001)
Examines how and why world societies have planned the arts, and explores how the arts reflect the changing urban, social, and economic atmosphere.
Includes bibliographical references (p. [293]-326) and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Art and state.;Arts and society.;City planning; 20; 2